Cryptology and Network Security 13th International Conference, CANS 2014, Heraklion, Crete, Greece, October 22-24, 2014. Proceedings - Gritzalis, Dimitris; Kiayias, Aggelos; Askoxylakis, Ioannis (Security and Cryptology, 2014)
This book constitutes the refereed proceedings of the 13th International Conference on Cryptology and Network Security, CANS 2014, held in Heraklion, Creete, Greece, in October 2014. The 25 revised full papers presented together with the abstracts of 3 invited talks were carefully reviewed and selected from 86 submissions. The papers cover topics of interest such as encryption; cryptanalysis; malware analysis; and privacy and identification systems as well as various types of network protocol design and analysis work.